2006
DOI: 10.1007/s10342-006-0111-0
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of spruce (Picea abies) and beech (Fagus sylvatica) forest stands to storms and consequences for silviculture

Abstract: The form and magnitude of storm damage and stand disclosure patterns were assessed in 332 randomly chosen pure and regular stands of spruce (Picea abies L.) and beech (Fagus sylvatica L.) after storm LOTHAR, within a region of the Swiss Midlands. This data was analysed in relation to maximal wind speed, measured with Doppler radar techniques and other influential factors such as relief, allometric characteristics, silvicultural history, and neighbourhood. In addition, storm damage, assessed from aerial photogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
3
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(171 citation statements)
references
References 20 publications
11
154
3
3
Order By: Relevance
“…Thus yield models are generally not appropriate for projecting stand development, or only under certain conditions. The difficulty is that such mortality events from disturbances are stochastic (Drössler and Lüpke, 2005;Quine and Bell, 1998;Schütz et al 2006;Zeibig et al, 2005) and assessing the risk occurrence implies different methodological probabilistic from those used to estimate yield alone. For instance, it needs largely corresponding areas covering hundreds of hectares, way beyond the usual reference for yield plots.…”
Section: Resultsmentioning
confidence: 99%
“…Thus yield models are generally not appropriate for projecting stand development, or only under certain conditions. The difficulty is that such mortality events from disturbances are stochastic (Drössler and Lüpke, 2005;Quine and Bell, 1998;Schütz et al 2006;Zeibig et al, 2005) and assessing the risk occurrence implies different methodological probabilistic from those used to estimate yield alone. For instance, it needs largely corresponding areas covering hundreds of hectares, way beyond the usual reference for yield plots.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of silver fir in the lower and middle layer observed in our study is the direct consequence of this lack of saplings and virtually no ingrowth into these layers. As for Norway spruce, the overall significant decrease of its proportion in all stand layers seems to be the result of multiple factors associated with the recent climate changes such as increasing temperature, lower precipitation rates, more frequent severe disturbances and a more intense impact of bark beetle [11,[62][63][64]. Despite the still relatively high proportion of Norway spruce (24% of the growing stock) in the locality investigated in our study, we recorded a low density of seedlings and saplings, indicating a serious problem for the maintenance of this tree species in studied stands.…”
Section: Discussionmentioning
confidence: 99%
“…In general, broadleaves are regarded as being more stable than conifers (Bryndum, 1986;Holmsgaard, 1986), probably because broadleaves are usually leafless in winter, the period where most storms occur. Several authors report a higher stability of mixed species stands as compared to monocultures (Grodzki et al, 1999;Lekes and Dandul, 2000;Schütz et al, 2006;Slodicak, 1995) but others argue that damage to a mixed species stand will only be reduced equal to the share of the stable species (Lüpke and Spellmann, 1997). Dhôte (2005) also concluded that tree species identity is more important in predicting wind damage to mixed stands than species richness.…”
Section: Stand Compositionmentioning
confidence: 99%
“…This is because a thinned stand, at least for the first 3-5 y after thinning, has increased canopy roughness (Dhôte, 2005;Schutz et al, 2006), which allows the wind to penetrate the canopy, and less wind energy is dissipated by the mechanical contact between crowns (Milne, 1991). In addition, trees that have grown in dense stands are poorly adapted to wind movement and therefore have poor anchorage strength until they can respond to the increased loading by strengthening their stems and root systems (Nicoll and Ray, 1996;Schütz et al, 2006;Stokes et al, 1997). One of the principles of forest fuel reduction treatments is to decrease crown density to reduce crown fire potential.…”
Section: Thinning and Pruningmentioning
confidence: 99%